Shared neural markers of decision confidence and error detection - Boldt, A; Yeung, N (Society for Neuroscience, 2015)
Empirical evidence indicates that people can provide accurate evaluations of their own thoughts and actions by means of both error detection and confidence judgments. This study investigates the foundations of these metacognitive abilities, specifically focusing on the relationship between confidence and error judgments in human perceptual decision making. Electroencephalography studies have identified the error positivity (Pe)—an event-related component observed following incorrect choices—as a robust neural index of participants' awareness of their errors in simple decision tasks. Here we assessed whether the Pe also varies in a graded way with participants' subjective ratings of decision confidence, as expressed on a 6-point scale after each trial of a dot count perceptual decision task. We observed clear, graded modulation of the Pe by confidence, with monotonic reduction in Pe amplitude associated with increasing confidence in the preceding choice. This effect was independent of objective accuracy. Multivariate decoding analyses indicated that neural markers of error detection were predictive of varying levels of confidence in correct decisions, including subtle shifts in high-confidence trials. These results suggest that shared mechanisms underlie two forms of metacognitive evaluation that are often treated separately, with consequent implications for current theories of their neurocognitive basis.